Impact of Continuous Assessment on Primary Education Students’ Attitude towards Learning in Tertiary Institutions in Anambra State, Nigeria - Umeji, Ifeoma Chinyere (Jurnal Indonesia Pendidikan Profesi Guru, 2025)
Background: Continuous Assessment (CA) plays a critical role in shaping students’ learning experiences and academic attitudes. In tertiary institutions, especially those training future educators, understanding the influence of CA on students' learning attitudes is essential for improving instructional practices and learning outcomes. Objective: This study investigated the influence of continuous assessment (CA) on primary education students' attitudes towards learning in tertiary institutions in Anambra State. It also examined contributing factors such as CA practices, resource availability, and student-lecturer ratios. Method: A descriptive research design was employed. Data were collected using a 40-item questionnaire validated by experts. The questionnaire was distributed via Google Forms and shared through social media platforms such as WhatsApp, Instagram, and Facebook groups. A total of 63 correctly completed responses were obtained. The data were extracted, coded in Microsoft Excel, and analyzed using SPSS software through mean and standard deviation calculations. Result: Findings show that CA has a positive impact on students' attitudes by offering regular feedback, fostering self-awareness, and reducing test anxiety. Nonetheless, effective implementation of CA is challenged by limited resources, time constraints, and large student-lecturer ratios. Conclusion: While continuous assessment contributes significantly to improving students' attitudes toward learning, systemic issues must be addressed to maximize its benefits. Contribution: This study provides valuable insights for educational stakeholders on the strengths and challenges of implementing continuous assessment in tertiary education. It underscores the need for collaborative efforts to improve resource allocation and lecturer support. Further research is recommended to investigate other variables affecting students’ learning attitudes in higher education contexts.